Experimental and theoretical analysis of Landauer erasure in nano-magnetic switches of different sizes. (January 2016) - Martini, L.; Pancaldi, M.; Madami, M.; Vavassori, P.; Gubbiotti, G.; Tacchi, S.; Hartmann, F.; Emmerling, M.; Höfling, S.; Worschech, L.; Carlotti, G.
Abstract: Bistable nano-magnetic switches are extensively used in storage media and magnetic memories, associating each logic state to a different equilibrium orientation of the magnetization. Here we consider the issue of the minimum energy required to change the information content of nano-magnetic switches, a crucial topic to face fundamental challenges of current technology, such as power dissipation and limits of scaling. The energy dissipated during a reset operation, also known as "Landauer erasure", has been accurately measured at room temperature by vectorial magneto-optical measurements in arrays of elongated Permalloy nanodots. Both elliptical and rectangular dots were analysed, with lateral sizes ranging from several hundreds to a few tens of nanometers and thickness of either 10 nm or 5 nm. The experimental results show a nearly linear decrease of the dissipated energy with the dot volume, ranging from three to one orders of magnitude above the theoretical Landauer limit of kB T×ln(2). These experimental findings are corroborated by micromagnetic simulations showing that the significant deviations from the ideal macrospin behavior are caused by both inhomogeneous magnetization distribution and edge effects, leading to an average produced heat which is appreciably larger than that expected for ideal nanoswitches. Graphical abstract: Highlights: We test the Landauer limit for nano-magnetic switches. Results of magneto-optical experiments and micromagnetic simuations are compared. Edge-effects and structural imperfections cause dissipation in excess of the Landauer limit.